2016
DOI: 10.3389/fonc.2016.00149
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Analytics for Prostate Radiotherapy

Abstract: Radiation therapy is a first-line treatment option for localized prostate cancer and radiation-induced normal tissue damage are often the main limiting factor for modern radiotherapy regimens. Conversely, under-dosing of target volumes in an attempt to spare adjacent healthy tissues limits the likelihood of achieving local, long-term control. Thus, the ability to generate personalized data-driven risk profiles for radiotherapy outcomes would provide valuable prognostic information to help guide both clinicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 161 publications
0
26
0
1
Order By: Relevance
“…These modeling methods are various, and the neural network and kernel-based methods are widely used. Figure 1 shows that the toxicity prediction results using principle component analysis (PCA) [4]. 48-86%, 35-91%, and 17-79%, respectively, were showed through this study (Figure 2).…”
Section: Prostate Cancermentioning
confidence: 58%
See 2 more Smart Citations
“…These modeling methods are various, and the neural network and kernel-based methods are widely used. Figure 1 shows that the toxicity prediction results using principle component analysis (PCA) [4]. 48-86%, 35-91%, and 17-79%, respectively, were showed through this study (Figure 2).…”
Section: Prostate Cancermentioning
confidence: 58%
“…Especially, machine learning is widely used [4][5][6]. Radiotherapy is a treatment method using radiation for cancer treatment based on a patient treatment planning for each radiotherapy machine.…”
Section: Definition Of Big Data and Each Clinical Application Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the heterogeneity of patient populations, it is important 1230 that datasets are large enough to include enough records to reflect the underlying patient population (Coates et al, 2016). Coates et al Coates et al (2016) provide a review of big data-mining techniques that have been applied to radiotherapy outcome modeling. They found that a major limitation in modern outcome modeling is the difficulty in grouping together datasets from multiple 1235 institutions, mainly due to patient privacy and security concerns.…”
Section: Big Data In Prostate Radiotherapymentioning
confidence: 99%
“…Ils ont ainsi intégré les histogrammes dose-volume et ont entraîné trois réseaux neuronaux pour prédire la nocturie, les rectorragies et l'évolution de la concentration sérique d'antigène spécifique de la prostate. La sensibilité et la spécificité restent cependant médiocre (55 %), mais des études plus récentes les ont significativement améliorées (jusque 68 % dans le modèle prédictifs des rectorragies de Tomatis et al) [25][26][27].…”
Section: Réseaux Neuronauxunclassified